High blood galectin-3 level associated with risk of frailty in aging - Ji, Xueying; Jiang, Zhaoshun; Qiu, Yixuan; Yu, Jiaming; Zhang, Yan; Wang, Jiaofeng; Ye, Bo; Huang, Yuxin; Gu, Weidong; Huang, Yiqin; Chen, Jie; Bao, Zhijun (Frontiers in Endocrinology, 2023)
Background: Frailty is one of the most problematic expressions of population aging, but its underlying mechanism has not been fully elucidated. Circulating Galectin-3 (Gal-3) is involved in the pathogenesis of many age-related diseases. This study aims to explore the influence of circulating Gal-3 on the regulation of frailty and aging, and to identify the potential mechanism further.In this cross-sectional analysis, Fried frailty phenotype (FP) was assessed among 149 community elderly residents in Shanghai. Peripheral Blood Mononuclear Cells (PBMCs) were isolated by Ficoll-Paque density gradient method, and differentially expressed genes (DEGs) encoding transcription factors in frailty were detected by Illumina and bioinformatics analyzed with R software. Gene Ontology (GO) enrichment analyses and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed to explore the functional roles of these DEGs and the target genes related to frailty phenotypes. The serum Gal-3 concentration was tested by ELISA. Mouse frailty phenotype was used to construct an in vivo model of frailty, after which the serum levels of circulating Gal-3 and its gene expression levels in mice tissues were determined.Results: Participants' mean age was 72.04 ± 7.05 years. In total, 21.48 % were frail and 36.91 % were pre-frail. The mean serum Gal-3 concentration was 46.34 ± 17.99 ng/mL in frailty participants, 32.30 ± 8.14 ng/mL in pre-frail participants, and 26.00 ± 5.87 ng/mL in non-frailty individuals (P < 0.001). Significant positive correlations between serum Gal-3 level and FP score, SARC-F score, C-reactive protein (CRP), interleukin-6, etc. were observed. In addition, the KEGG pathway and GO enrichment analyses showed that the 265 DEGs in PBMCs of frailty participants were mainly related to inflammatory response, translation, RNA binding, protein binding, ribosome, and primary immunodeficiency.LGALS3 was identified as the overlapping gene between frailty-related DEGs and aging-related DEGs. And the elevated serum Gal-3 concentration in the in vivo model of frailty was consistent with the results in participants.In both community-dwelling older adults and aged mice, serum Gal-3 concentration was positively correlated with frailty. This circulating mediator may be a promising indicator of frailty.